STUDY ON THE COMPULSORY BRINGING OF PERSONS IN FRONT OF THE JUDICIAL AUTHORITIES IN CRIMINAL MATTERS - Radu - Florin GEAMĂNU (Challenges of the Knowledge Society)
The study will try to perform an in-depth analysis of the measure of compulsory bringing, assessing both the national legislation and the legislation of some European countries, namely: Austria, Bulgaria, Poland and the Netherlands. Due attention will be granted to the provisions of the current Criminal Procedure Code, which entered into force on the 1st of February 2014, as this piece of legislation brings some important changes regarding the compulsory bringing, some of them being the consequence of the convictions of Romania in front of the Strasbourg Court. Also, the paper will focus on case-law established by the European Court of Human Rights regarding articles 3 and 5 relating to the compulsory bringing. To close with, the study will give some conclusions regarding the conformity of the current Criminal Procedure Code of Romania with the standards imposed by the European Convention for the Protection of Human Rights and Fundamental Freedoms and by the case-law of the European Court of Human Rights.